WiderScreen 27 (1–2) 2024: Historian viihteellistäminen / The Popularization of History - (:unkn) unknown (My University, 2025)
Historiallisten tapahtumien viihteellistämisellä on pitkä perinne. Sosiaalisen median aikakaudella tämä ilmiö on saanut uusia muotoja esimerkiksi meemien ja digitaalisten pelien kautta. WiderScreenin erikoisnumero tuo esiin sekä kriittisiä kysymyksiä että uusia tutkimusmenetelmiä historian ja viihteen tarkasteluun. Numerossa tarkastellaan, miten kirjallisuus, elokuva, televisio, pelit ja sosiaalinen media käsittelevät historiaa viihteellisinä ilmiöinä. Viihteellistämisen vaikutuksia tarkastellaan laajasti eri näkökulmista, mukaan lukien propagandan käyttö, historiallisten kuvastojen vääristymät ja mediakulttuurin uudet ilmiöt.

The popularization of historical events has a long tradition. In the era of social media, this phenomenon has taken new forms through memes and digital games, among others. WiderScreen's special issue highlights both critical questions and innovative research methods for examining the relationship between history and entertainment. The issue explores how literature, film, television, games, and social media depict history as entertaining phenomena. The historical representations are examined from a wide range of perspectives, including the use of propaganda, distortions of historical imagery, and emerging trends in media culture.